Pituitary function in patients with primary and secondary empty sella - Steckel, Lucas; Gizewski, Elke R.; Kaser, Susanne (Frontiers in Endocrinology, 2025)
BackgroundDue to the increasing availability and sensitivity of neuroradiological imaging, the number of incidental findings of empty sella (ES) is rising, however, the clinical relevance is not clearly defined.MethodsIn this longitudinal, single-center study patients with first-time diagnosed primary or secondary empty sella were analyzed and followed up for five years. Hormone deficiencies were diagnosed by measuring basal pituitary and target organ hormone levels or dynamic stimulation tests.ResultsOverall, 119 patients, 97 with primary (PES) and 22 with secondary empty sella (SES) were included. At baseline, isolated or total pituitary insufficiency was detected in 34% of patients with PES and 63.6% of patients with SES. While hypogonadism was the most common finding in PES affecting 25.8% of patients, adrenal insufficiency was the most frequent finding in SES affecting 54.5% of patients. Only two patients with intact pituitary function at baseline, one with SES and one with PES, were diagnosed with hormone insufficiency during follow-up.ConclusionsHormone deficiency is common in empty sella, with males and patients with SES being at highest risk. In patients with intact pituitary function at time of diagnosis, the risk of developing hypopituitarism is low thus not justifying regular follow-up assessments.